Monte-Carlo Study of the Collective Behavior in Animal Group: A \(q\)-state Potts model - The, Nguyen Phuoc; Thanh, Ngo Van (Communications in Physics, 2015)
We study in this work the phase transition behaviour of animal groups. We assume that the individuals in the group have two classes of state. One is the internal state which can be either excited or non-excited. The other one is characterized by their orientation or direction of motion, it is so called the external state.The internal state plays an important role in the rules of interaction between the individuals.The system is put under a source of external perturbation called ``noise", the individuals can freely move from one site to another site on a two-dimension triangular lattice. We use the Monte-Carlo simulation technique for studying the behavior of the model with varying noise. For simplicity, we consider the orientation of individuals which has q states as in the Potts model. We show that the system has three phases which correspond to the uncollected, flocking and runaway behaviors at very low, medium and high noise, respectively. These phases are separated by two first-order transitions